MANAGEMENT OF EARLY GRAFT FAILURE POST CORONARY ARTERY BYPASS GRAFTING: A CASE REPORT - Heston Napitupulu; Lisca Namretta; Sheila Giusti; Maizul Anwar (JURNAL WIDYA MEDIKA, 2021)
Background: Early postoperative graft failure after coronary artery bypass grafting (CABG) is still a significant problem that results in high morbidity and mortality. It is associated with early graft thrombosis, anastomotic stenosis, bypass kinks, overstretching or tension, significant spasm, and incomplete revascularization. Case Report: 67 years-old male with Coronary Artery Disease involving three vessels (CAD 3VD) underwent CABG surgery. Direct post-operation electrocardiograph (ECG) shown changes in ST segments (elevation on anterior leads and depression on inferior leads) with a significant increase of cardiac markers level. Post-operative coronary angiography revealed an occluded left internal mammary artery (LIMA) graft and native left anterior descending artery (LAD) blockage. Patients’ hemodynamics was not stable, and was urgently underwent an off-pump redo CABG. Intraoperatively we found thrombus at LIMA and saphenous vein graft (SVG) – right coronary artery (RCA) grafts that were caused by atheroma and dissection on anastomotic side. Discussion: The diagnosis of myocardial infarction (MI) remains a clinical challenge since patients are unable to express classic clinical symptoms. Routine ECG combined with cardiac biomarkers are beneficial in diagnosing MI post CABG, and percutaneous coronary angiography (PTCA) is useful in detecting the patency of the grafts. Although percutaneous coronary intervention (PCI) is preferable in the case of anastomosis problem with stable hemodynamic, redo CABG shows more benefit in salvaging infarcted myocardium in patients with unstable hemodynamic. Conclusion: Redo CABG surgery with new or additional grafting may save myocardium and preserve its function in perioperative infarct caused by graft failure.